The constitutionality of the right to assembly and its impact on the formation of associations in Iraq: An analytical study. - مەجيد, سوز حەميد; كەريم, بژ ار شوكەت (Sulaimani Journal for Humanities, 2020)
The study dealt with the constitutionality of the right of assembly and its impact on the formation of associations. Constitution’s guarantee this freedom to citizens and guarantee them to exercise it. This is not possible without spreading the culture of this freedom among citizens and public authorities alike. The right of assembly was the basic nucleus from which civil society emerged, and there is no doubt that no country can survive without the support of civil society forces in all spheres of life.